Eumenes of Cardia : a Greek among Macedonians - Anson, Edward. (Mnemosyne, Supplements, 2015)
Eumenes of Cardia: A Greek Among Macedonians (2nd edition) updates the original work in light of a decade of scholarly activity and presents much new analysis influenced by this continuing scholarship. Eumenes of Cardia was a royal secretary who, in the years following the death of Alexander the Great became a major contender for power. Despite the fact that he had been chiefly an administrator rather than one of Alexander's elite military commanders, and that he was a Greek from the city of Cardia, as opposed to a native Macedonian, Eumenes came close to securing control of the Asian remnants of Alexander's empire. His history is important because our sources for the years immediately following the Conqueror's death are dominated by the Cardian's story. Moreover, his death marked in many respects the approaching end of the Macedonian dynasty of kings who had ruled Macedonia since the 8th c. BC, and his life illuminated both the nature of the Macedonian heritage and the possibilities of the new age ushered in by the conquests of the great Alexander.